The Social Fabric of a Team-Based M.B.A. Program: Network Effects on Student Satisfaction and Performance - Baldwin, Timothy T.; Bedell, Michael D.; Johnson, Jonathan L. (Academy of Management Journal, 1997)
The present study was an empirical analysis designed to measure the social networks of master of business administration (M.B.A.) students and the networks? relationships to attitudinal and performance outcomes. Results from 250 students indicated that centrality in friendship, communication, and adversarial networks affected both student attitudes and grades. Moreover, an analysis of 62 assigned teams showed that relationships within and between teams also had significant effects on student perceptions of team effectiveness and objective team performance. Implications for student networks and suggestions for future research are discussed.